The Effect of Cinnamon Extract on Blood Sugar Levels in Type 2 Diabetes Mellitus Patients: A Meta-Analysis - Agustia, Dilma'aarij; Muda Marpaung , Sutan Sahala; Lubis, Dita Anggriani (Jurnal Kebidanan dan Kesehatan Tradisional, 2025)
Background: Diabetes Mellitus is still a global problem today. This is demonstrated by the 2018 global data, which indicates that diabetes mellitus is the ninth leading cause of mortality and that the number of people with the disease has quadrupled over the last three decades. This research aims to estimate the magnitude of the impact intervention in giving cinnamon extract based on the findings of several earlier research. Methods: This study uses secondary data sources with a systematic approach utilizing meta-analyses and PICO.  The population consists of patients with type 2 diabetes., Intervention is giving extra cinnamon. The outcome is blood sugar levels. Keywords for the articles searched were as follows: “cinnamon” AND “Diabetes mellitus type 2” AND “randomized controlled trial”. The articles that are part of it. This research uses a randomization-controlled trial study design and is a full-text article. Utilizing the PRISMA flow diagram, articles are gathered. They used the Review Manager 5.3 program to analyze. Results: Research indicates that giving individuals with type 2 diabetes mellitus additional cinnamon eating interventions significantly lowers their blood sugar levels (Standardized Mean Difference = -0.74; 95% CI = -1.67 to 0.18; p= 0.110). Conclusion: The consumption of cinnamon supplements has been shown to significantly lower blood glucose levels in individuals with type 2 diabetes mellitus. Therefore, cinnamon supplementation may be considered as a complementary strategy in the dietary management of type 2 diabetes, alongside standard pharmacological and lifestyle interventions.